ENHANCING THE VISITOR EXPERIENCE A STUDY ON THE DIVERSIFICATION OF TOURISM PRODUCTS IN SRI LANKA - Moramudali, Wageesha Kalhari (Department of Economics, Faculty of Arts, University of Colombo, 2018)
Purchasing a tourism product is different from purchasing a consumer good. Tourism product contains of attributes such as service, experience, persuasion, involvement, and most importantly revisit. Destinations are supposed to fulfill all those desires of each and every visitor. Eventually, needs and wants of visitors have shown dynamic changes due to competition among destinations. In today’s saturated markets customers look for experience rather than destination driven products. The creation of experience should consist of entertainment, educational, aesthetics and escapist elements. Theoretically, a product has an s - curve with stages of growth, maturity, saturation and decline in sales and profits and it seems to hold true even for tourism products imposing that product development and new product innovations is important in tourism. Sri Lanka is marketed for nature based tourism, cultural tourism and historical tourism. In a highly competitive market those elements are not enough to stay competitive. Therefore, this research study intended to explore possible new product development for the tourism industry of Sri Lanka. The Quantitative approach has been employed in this research. 70 online questionnaires were administered to iden tify tourist satisfaction with regard to existing tourism products. Findings of this study revealed that the visitor satisfaction for activities for kids, organized excursions, traditional dance and music, and for contact with local communities is at a lower level. Following niche product developments are proposed to make tourism a larger contributor to the economy: Galle fort trishaw ride, temple stay, honeymoon packages , thatched houses and performance of traditional music and dance.
Keywords: creative Tourism, Destination marketing, product innovation